Chlorate poisoning in beef cattle - Blakley, Barry R. (Canadian Veterinary Medical Association, 2007)
A disease syndrome characterized by hemolysis, methemoglobinemia, methemoglobinuria, and death was observed in a herd of purebred Limousin beef cattle grazing on pasture in November in Alberta. Improper disposal of the nonselective herbicide, sodium chlorate, was identified as the causal agent. Highly variable blood methemoglobin levels reflected differences in herbicide consumption.